2008
DOI: 10.1002/macp.200800371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Species on the Structures and Properties of Salt‐Containing PEO/Montmorillonite Nanocomposites

Abstract: This contribution describes the preparation and characterization of PEO/montmorillonite nanocomposite gels and films containing various lithium and sodium salts. The objective is to understand how the size and diffusion abilities of different ionic species added to these systems alter the crystallinity of the polymer, and affect the mechanical properties and ionic conductivities of the solid nanocomposites. The network strength of the polymer/clay dispersions influences decisively the crystallinity of the PEO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…Nanocomposites of poly(ethylene oxide) with montmorillonite have been extensively studied in the past decade [ 5 , 191 , 192 , 193 , 194 ]. It has been recently shown that the ionic strength in PEO-MMT nanocomposite gels, dictated by addition of various Li + and Na + salts, affects the extent of internal orientation of such systems when subjected to elongational flow [ 194 ].…”
Section: Polymer/clay Nanocompositesmentioning
confidence: 99%
“…Nanocomposites of poly(ethylene oxide) with montmorillonite have been extensively studied in the past decade [ 5 , 191 , 192 , 193 , 194 ]. It has been recently shown that the ionic strength in PEO-MMT nanocomposite gels, dictated by addition of various Li + and Na + salts, affects the extent of internal orientation of such systems when subjected to elongational flow [ 194 ].…”
Section: Polymer/clay Nanocompositesmentioning
confidence: 99%
“…Contrary to what can be observed in this work, it has been shown in the past that in many aqueous systems clay nanoplatelets orient with the surface parallel to the plane of the film and stack on top of each other forming a layered structure 18. For example, it has been proven that in poly(ethylene oxide) (PEO)/MMT nanocomposite films, prepared via a LBL approach from aqueous dispersions, the clay platelets predominantly orient with the surface parallel to the plane of the film leading to observation of anisotropy in SAXS and SEM experiments 18, 44, 45. Clearly, such a predominant platelet orientation is not detected for the PIB/MMT film discussed here.…”
Section: Resultsmentioning
confidence: 99%
“…Основні дослідження в цьому аспекті протягом останнього часу були спрямовані на удосконалення методів синтезу і характеристику фізичних власти-востей полімерних нанокомпозитів [7,8,11,13]. Вуг-лецеві нанотрубки (ВНТ) становлять значний інтерес для багатьох технологій [3].…”
Section: аналіз останніх публікацій і дослідженьunclassified